Enhanced Radio Access Technologies for Next Generation Mobile Communication - Park, Yongwan; Adachi, Fumiyuki (Springer Netherlands : Imprint: Springer, 2007)
Enhanced Radio Access Technologies for Next Generation Mobile Communication presents a comphrenhensive overview of the latest technology developments in the field Mobile Communications. This monograph focuses on the fundamentals of mobile communications technology and systems, including the history and service evolution of mobile communications and environments. Further to this, CDMA technology including spread spectrum, orthogonal and PN codes are introduced. Other important aspects include fundamentals of single carrier CDMA technologies, DS CDMA, Broadband CDMA with frequency domain equalizer, and multi-carrier CDMA technology for high speed data transmission including MC-DS/CDMA, MC-CDMA. Finally aspects of modern cellular systems such as cdma2000/1xEv-Do/1xEv-Dv and WCDMA/HSDPA are introduced and existing and developing wireless data services, such as Wi-Fi, Bluetooth, UWB, WiBro/Mobile WiMAX, and digital broadcasting services like DVB, DMB, ISDBT are described. Enhanced Radio Access Technologies for Next Generation Mobile Communication is written for academics as well as IT and Communications engineers who are starting their careers and for working professionals. It can be used as a textbook for students and training for new and current employees.